Pellet structure formed from thermoplastic composition core and calcium stearate shell

By covering the calcium stearate powder coating on the polyether ether ketone polymer pellets, the problem of difficult demolding of thermoplastic compositions during injection molding is solved, and the pellets are easily demolded under gravity and the material properties are unchanged. Effect.

CN119220047APending Publication Date: 2024-12-31VICTREX HIGH PERFORMANCE MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310790223.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the injection molding process, the thermoplastic composition is prone to get stuck in the mold, resulting in difficulty in demolding and additives affect material properties.

Method used

Granular materials with core-shell structures are used, where the core is formed of polyether etherketone polymer (PEEK), the shell is covered with a calcium stearate powder coating, with a thickness ranging from 5 μm to 45 μm and a calcium stearate content of 0.03 wt % to 0.05 wt% to ensure that the pellets are easily demolded under gravity.

Benefits of technology

The injection molded parts are easily demolded under gravity and do not affect the physical and mechanical properties of the pellets, reducing waste generation and improving mold release efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220047A_ABST
    Figure CN119220047A_ABST
Patent Text Reader

Abstract

The present disclosure discloses pellets for injection molding compositions wherein the pellets have a substantially elongated shape and comprise a core-shell structure wherein: i) the core of the pellets is formed from a thermoplastic composition comprising a polyetheretherketone polymer (PEEK polymer), the core having a width dimension in the range of about 1 mm to about 4 mm, and ii) the shell of the pellet is formed from a powder coating comprising calcium stearate wherein the thickness of the shell is in the range of about 5 [mu] m to about 45 [mu] m wherein the calcium stearate is present in the range of about 0.03 wt% to about 0.05 wt%, and wherein the longitudinal dimension of the pellet is in the range of about 1 mm to about 6 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to pellets coated with a calcium stearate shell, particularly wherein the pellets are formed from a polyetheretherketone polymer (PEEK polymer) core. Background Art

[0002] The use and production of polymer pellets is common because pellets represent a convenient material form for handling and dispensing of polymer products. In addition, pellets are a convenient starting material for a variety of downstream uses such as injection molding.

[0003] Injection molding using pellets will typically require prying open or otherwise removing or demolding the molded product from the injection mold.Some thermoplastic compositions tend to get stuck in the injection mold, particularly when high temperatures are used during the molding process, because the surface of the molded part may remain sticky or tacky.

[0004] Some pellets introduce additives into the internal composition of the pellets. However, this inevitably affects the material properties of the pellets themselves, as well as the material and physical properties of the injection molded parts made from the pellets.

[0005] The purpose of the present disclosure is to try to alleviate the above mentioned problems. Summary of the invention

[0006] In a first aspect, there is provided a pellet for injection molding a composition, wherein the pellet has a substantially elongated shape and comprises a core-shell structure, wherein:

[0007] i) the core of the pellet is formed from a thermoplastic composition comprising a polyetheretherketone polymer (PEEK polymer), the core having a width dimension in the range of about 1 mm to about 4 mm, and

[0008] ii) the shell of the pellet is formed from a powder coating, the powder coating comprising calcium stearate, wherein the shell has a thickness in the range of about 5 μm to about 45 μm,

[0009] wherein the calcium stearate is present at about 0.03 wt% to about 0.05 wt%, and wherein the longitudinal dimension of the pellets is in the range of about 1 mm to about 6 mm. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1a A schematic diagram of a pellet according to the first aspect of the present disclosure is shown, viewed in the direction of the longitudinal axis of the pellet and thus showing a circular cross section.

[0011] Figure 1b Shown is a schematic diagram of a pellet according to the first aspect of the present disclosure viewed from the side and showing the length of the elongated pellet and thus showing a rectangular cross-section.

[0012] Figure 2a and 2b Shown are photographs of pellet cores and coated pellets according to the first aspect of the present disclosure. DETAILED DESCRIPTION

[0013] In a first aspect, there is provided a pellet for injection molding a composition, wherein the pellet has a substantially elongated shape and comprises a core-shell structure, wherein:

[0014] i) the core of the pellet is formed from a thermoplastic composition comprising a polyetheretherketone polymer (PEEK polymer), the core having a width dimension in the range of about 1 mm to about 4 mm, and

[0015] ii) the shell of the pellet is formed from a powder coating, the powder coating comprising calcium stearate, wherein the shell has a thickness in the range of about 5 μm to about 45 μm,

[0016] wherein calcium stearate is present at about 0.03 wt% to about 0.05 wt%, and wherein the longitudinal dimension of the pellets is in the range of about 1 mm to about 6 mm.

[0017] It will be understood that width refers to the dimension of the pellet that is perpendicular or substantially perpendicular to the elongated (ie longitudinal) dimension. For example, where the pellet is cylindrical, the width will represent the diameter of the circular cross-section of the pellet.

[0018] Advantageously, the inventors have determined that the introduction of a shell coating on the pellets with as little as 0.03wt% to 0.05wt% of powdered calcium stearate is sufficient to allow easy and reliable demoulding of injection molded parts prepared from a molding composition comprising the pellets. This corresponds to a shell thickness of about 5μm to about 45μm. The calcium stearate shell can be easily applied to the surface of the pellet core by mixing. Further advantageously, the shell comprising calcium stearate is only arranged on the outer surface of the pellet core. Therefore, calcium stearate is not introduced into the interior of the pellet or as part of the thermoplastic composition, so the physical and mechanical properties of the pellet are substantially unaffected by the presence of the calcium stearate shell. When the pellets according to the first aspect are used in an injection molding process, the shell covering the pellets will confer the following advantages: the resulting injection molded parts are easy to demould only under gravity without applying additional pulling forces.

[0019] It should be understood that the essence of "powder" is intended to mean a solid material whose particle size / size is significantly smaller than the pellet size, preferably several orders of magnitude smaller than the pellet. The D50 particle size of the calcium stearate forming the powder coating is about 8 μm to about 10 μm, and the D90 particle size of the calcium stearate is about 18 μm to about 20 μm. In other words, 50% of the calcium stearate particles are less than about 8 μm to about 10 μm in size, and 90% of the calcium stearate particles are less than about 18 μm to 20 μm in size. The median particle size of calcium stearate is preferably about 5 to about 15 μm, more preferably about 8 to about 12 μm. The particle size can be measured by laser diffraction. This particle size allows calcium stearate to adhere to the pellet surface and preferably form a substantially uniform coating.

[0020] Preferably, the shell comprises 1 to 3 coating layers, wherein the thickness of each layer is in the range of about 5 μm to about 15 μm. Thus, the thickness of the shell in the granulate may be about 5 μm to about 45 μm. More preferably, the shell thickness of the granulate is in the range of about 15 μm to about 25 μm. Considering the median particle size of about 5 μm to about 15 μm, more preferably about 8 μm to about 12 μm, each layer of the shell formed by the calcium stearate powder preferably constitutes a single particle deposition.

[0021] Preferably, calcium stearate is present in an amount of about 0.04wt%. Preferably, the shell is substantially composed of a powder coating, which is made of calcium stearate. It will be understood that 0.04wt% refers to the amount of mass relative to the mass of the complete pellet. The use of about 0.04wt% calcium stearate provides a favorable compromise, wherein the amount of calcium stearate is used in injection molding, and substantially all articles prepared by injection molding are easy to demould under gravity alone. In addition, it is beneficial that calcium stearate greater than this amount is not required, so the inventors have confirmed the amount of highly material-effective calcium stearate that produces minimal waste when used in injection molding. It will be understood that additional calcium stearate (e.g., excessive, not forming part of the shell) can be present in a batch of pellets, and the batch contains a plurality of pellets according to the first aspect.

[0022] Preferably, the PEEK polymer is semi-crystalline. This provides the advantage that when at room temperature the pellets are structurally rigid, but not brittle, which means that vigorous mixing can be used to apply the calcium stearate coating, which is advantageous for applying a substantially uniform coating.

[0023] Preferably, the PEEK polymer has a repeating unit of formula I:

[0024] -O-Ph-O-Ph-CO-Ph-

[0025] wherein Ph represents a phenylene moiety. In this embodiment, all phenylene groups are 1,3 substituted and / or 1,4 substituted to adjacent ether and / or carbonyl groups.

[0026] Preferably, the pellets are substantially cylindrical and therefore preferably have a substantially circular cross-section. Having a substantially uniform circular surface on the pellets allows for a uniform application of the powder coating, i.e. this would be more difficult with pellets having more edges. Furthermore, this is a suitable shape for pellets that can be prepared by extrusion. Preferably, at least one end of the pellet (which is substantially cylindrical) is wedge-shaped. Preferably, both ends of the pellets are wedge-shaped.

[0027] Preferably, the diameter of the pellets is in the range of about 2.5 mm to about 3.5 mm, and wherein the longitudinal dimension of the pellets is in the range of about 2 mm to about 4 mm. Further preferably, the diameter of the pellets is about 2.7 to about 3.1 mm, and the longitudinal dimension of the pellets is in the range of about 2.5 mm to about 3.5 mm, more preferably about 2.8 mm to about 3.4 mm. These dimensions are particularly preferred for substantially cylindrical pellets.

[0028] Preferably, the mass of the pellets is in the range of about 0.02 g to about 0.05 g, more preferably, in the range of about 0.02 to about 0.04 g, and more preferably about 0.03 g.

[0029] Preferably, the pellets consist essentially of calcium stearate, which forms the shell of the pellets, and PEEK polymer, which forms the core of the pellets.

[0030] The pellets of the first aspect may be provided as a plurality of pellets for use as a molding composition, preferably wherein the molding composition comprises up to about 100 wt % of the plurality of pellets, preferably up to about 99.9 wt % of the plurality of pellets, preferably up to about 95.0 wt % of the plurality of pellets.

[0031] Preferably, the powder coating of calcium stearate is a dry solid powder that is substantially continuous over the entire surface of the pellets. A uniform coating of calcium stearate on the pellet surface reduces the likelihood of a plurality of such pellets agglomerating or clumping together, and also reduces the likelihood of injection molded parts sticking to the mold after molding. In addition, a uniform coating promotes excellent adhesion between the calcium stearate and the pellet surface, which means that the calcium stearate is less likely to fall off or be consumed during handling, transportation, and processing of the coated pellets.

[0032] Preferably, the powder coating adheres to the pellet surface only by contact forces. It will be understood that "contact forces" refer to the forces that occur when any two objects or materials are in physical and direct contact with each other, for example, weak electrostatic attraction and / or van der Waals forces. In other words, advantageously, the calcium stearate powder is disposed on substantially the entire surface of the pellet without the need for other additives or binders.

[0033] Preferably, the thermoplastic composition further comprises about 0.1 wt% to about 50 wt% of a filler, preferably about 0.1 wt% to about 30 wt% of a filler, preferably wherein the filler is carbon black, glass fiber, a mineral filler or a combination of two or more thereof, preferably wherein the filler is carbon black. Such fillers are suitable for use in thermoplastic compositions.

[0034] More preferably, the filler comprises carbon black and the amount thereof is in the range of about 0.5% wt to about 5% wt, and even more preferably in the range of about 1 wt% to about 2 wt%.In a preferred embodiment, the filler consists substantially or essentially of carbon black.

[0035] Preferably, a plurality of pellets comprising the pellets according to the first aspect are provided. The plurality of pellets may contain additional loose (e.g., excess) calcium stearate that is not incorporated as part of the shell. Preferably, at least about 50wt% of the calcium stearate forms the shell, preferably about 50wt% to about 100wt% of the calcium stearate forms the shell, preferably about 60wt% to about 80wt% of the calcium stearate forms the shell. It will be understood that some of the loose calcium stearate that forms part of a batch of a plurality of pellets according to the first aspect may not form part of the pellet shell. This helps the demoulding process and allows for a more uniform coverage of the calcium stearate present, since there may be an excess of calcium stearate available for forming a powder coating.

[0036] Preferably, at least 99% of the pellets in the plurality of pellets have a length of about 2 mm to about 4 mm. This has the benefit of improving the ease of handling and processing the pellets in downstream uses, particularly in injection molding processes, i.e., since the narrow distribution of pellet sizes promotes uniform melting of the pellets during injection molding. This, in turn, promotes a uniform structure in the subsequently formed injection molded part.

[0037] The present disclosure relates to a method of preparing a molding composition for injection molding, the method comprising:

[0038] a) providing a plurality of pellet cores having a substantially elongated shape and formed from a thermoplastic composition and having a width dimension in the range of about 1 mm to about 4 mm, wherein the thermoplastic composition comprises a polyetheretherketone polymer (PEEK polymer), wherein a longitudinal dimension of each pellet is in the range of about 1 mm to about 6 mm,

[0039] b) providing from about 0.05 wt % to about 0.07 wt % of calcium stearate,

[0040] c) mixing a plurality of granule cores with calcium stearate to form a plurality of granules having a core-shell structure, wherein the shell is formed of a powder coating comprising calcium stearate, wherein the thickness of the shell is in a range of about 5 microns to about 45 microns, and wherein the calcium stearate is present in the shell at about 0.03 wt % to about 0.05 wt %.

[0041] Preferably, the process comprises calcium stearate and / or any of the other characteristics of the coating and / or granules described herein.

[0042] Figure 1a A schematic diagram of a coated pellet 100 having a core-shell structure according to the first aspect is shown. The figure shows a cross section through the long axis of the pellet, so it shows a circular cross section. The pellet comprises: a core 102 comprising a PEEK polymer; and, a shell 104 comprising a first calcium stearate layer. In some embodiments, the shell may comprise 2 or 3 layers: an optional second layer 106 and a third layer 108 are shown in dashed lines. If there are multiple layers, each layer may have a different thickness. Preferably, each layer is about 5 μm to about 15 μm thick. Preferably, the pellet diameter is in the range of about 2.5 mm to about 3.5 mm; in this case, the diameter corresponds to the diameter of the core 102 of the substantially cylindrical pellet 100.

[0043] Figure 1b Shown from a side view Figure 1a The same pellet in the figure, i.e. the length of the cylinder can be observed. Therefore, the figure shows a rectangular cross-section.

[0044] Example

[0045] Experiments were conducted to compare the mixing conditions that can produce pellets or pellets having a core-shell structure and shape according to the first aspect, and further experiments were conducted to test the demoulding ability of the calcium stearate coated pellets when injection molding was used. The pellets used in the test contained black grade PEEK 450G903, which contained 1% to 2% carbon black by mass.

[0046] Table 1 below shows the influence of different mixing conditions on the quality of the calcium stearate shell on the surface of the obtained pellet core, and the ease with which the injection molded parts made of those pellets can be demoulded. During each test, the uncoated PEEK pellet core was mixed with a certain amount of dry calcium stearate powder in a container. A Matcon blender system was used and a 360° rotation was defined as one circle. Mixing speed (turns / min) and mixing time were mixing parameters. The calcium stearate used had a Sauter mean diameter (SMD) of 5.41 μm, a volume median diameter (VMD) of 9.93 μm, wherein the D50 particle size of calcium stearate was 8.57 μm, the D90 particle size of calcium stearate was 19.10 μm, and the D99 particle size of calcium stearate was 29.48 μm.

[0047] Demolding tests were performed using an ISO tensile bar mold according to ISO tensile 527 type 1A. In these tests, 10 injection molding tests were performed using pellets produced from each of the 12 tests in Table 1. For each of the 10 injection molding tests, the number of times the 10 test bar molds fell freely from the mold under gravity alone was recorded. Thus, for example, a score of "10" in the "Reaction 2" column of Table 1 means that for this test, all 10 molded bars fell freely under gravity without applying additional assistance / force.

[0048] Table 1

[0049]

[0050] Table 2 below shows the qualitative criteria used to determine the "Distribution Quality" score under the "Reaction 1" entry of Table 1.

[0051] Table 2

[0052] Score Mixing quality of calcium stearate (CaSt) and PEEK-based pellets 1 Very little CaSt 2 Very little CaSt 3 The distribution of CaSt is not uniform in some areas. The amount of CaSt is insufficient. 4 The distribution of CaSt is not uniform in some areas. The amount of CaSt can be 5 The distribution of CaSt is not uniform in a few areas. The amount of CaSt is OK. 6 The CaSt distribution is good. The amount of CaSt is OK. 7 The distribution of CaSt is not uniform in some areas. The amount of CaSt is sufficient. 8 The distribution of CaSt is uneven in a few areas. The amount of CaSt is sufficient. 9 The CaSt is well distributed. The amount of CaSt is sufficient. 10 The CaSt distribution is excellent. The amount of CaSt is sufficient.

[0053] As can be seen from Table 1, there is a relationship between mixing quality and demoulding quality. For example, tests 11 and 12 produced pellets with demoulding properties that were better than tests 9 and 10, which used the same amount of calcium stearate, but the stearate was mixed into the pellets at a lower speed. Therefore, more intense mixing (i.e., mixing at high speed) advantageously improved demoulding quality. It can also be seen from comparative tests 9 to 12 that the distribution quality of CaSt on the pellet surface was improved by more intense mixing. Therefore, the more uniform distribution of CaSt powder on the pellet surface resulted in easier demoulding.

[0054] Figure 2a As a reference, an uncoated pellet core 200 made of PEEK 450G903 and containing 1 to 2% by mass of carbon black is shown. As can be seen, the pellet is cylindrical and has one wedge-shaped end (on the upper side of the pellet towards the top of the figure).

[0055] Figure 2b Coated pellets 202 having a core-shell structure are shown. Pellets 202 are pellets produced during Run 12 of Table 1. It can be seen that the coverage of calcium stearate forming the shell is substantially uniform over the pellet surface. Pellets 202 shown contain a shell having 0.04 wt% calcium stearate.

[0056] Table 1 also shows that the most profound effect on demoulding quality comes from the amount of calcium stearate coating the pellet surface. When calcium stearate was used in amounts of 0.04% and below (Trials 1 to 8), demoulding scores varied between 0 and 4. In contrast, in Trials 9 to 12, where 0.06% was used, demoulding scores varied between 7 and 10 (the highest possible score).

[0057] Table 1 also shows how the coverage of the calcium stearate shell depends on the mixing conditions. The inventors have determined that as much as about 30% to 40% of the calcium stearate introduced into the mixture can be lost during mixing (e.g., it coats the blades of the mixing equipment). When low levels (i.e., as little as 0.02%) of calcium stearate are used, longer mixing times can exacerbate this effect, as can be seen in Test 4: A "Reaction 1" score of 1 indicates very little coverage of the calcium stearate, i.e., corresponding to a thin and / or small amount of shell on the pellets.

[0058] Furthermore, the release quality was not dependent on the mixing time when 0.06% calcium stearate was used, as confirmed by Tests 11 and 10. Thus, 0.06% calcium stearate did not need to be mixed for longer than 8 minutes to provide a uniform and uniform coating that established excellent release properties.

[0059] The inventors unexpectedly determined that when calcium stearate was added in an amount greater than 0.06%, there was no further improvement in demoulding quality, and therefore no significant other benefits were found. In addition, the use of larger amounts of CaSt (e.g., greater than 0.1% by mass) resulted in greater losses of CaSt during mixing, which was undesirably wasteful. Further unexpectedly, the inventors have confirmed that when 0.06% calcium stearate was used, the relationship between mixing time / speed and calcium stearate loss was reversed: for example, it can be seen that the best coverage was obtained with higher mixing speeds and times (test 12) compared to test 4, where the worst coverage was observed with higher mixing speeds / times.

[0060] The inventors have confirmed that when calcium stearate is used in an amount up to about 0.06%wt, consistently, about 30% to 40% of the mass of calcium stearate initially introduced during mixing does not form part of the shell in the final core-shell structured pellets. Thus, it was found that trials 9 to 12 in Table 1 produced pellets having a shell containing about 0.04wt% calcium stearate. Nevertheless, it will be understood that unintroduced, excess calcium stearate can still loosely wrap a plurality of pellets, thereby forming a batch prepared according to the above mixing method.

[0061] The inventors have also confirmed that the advantages of the calcium stearate coating corresponding to the results described herein are also applicable to other types of PEEK pellets, for example, PEEK polymers other than PEEK 450G903 used in the examples described herein. Therefore, the use of calcium stearate can be easily applied to a variety of different PEEK pellets.

[0062] In this specification, embodiments have been described in a manner that enables a clear and concise description to be written, but it is intended and will be understood that the embodiments may be combined or separated differently without departing from the present invention. For example, it should be understood that all preferred features described herein apply to all aspects of the present invention described herein, and vice versa. For example, all preferred features of the composite material apply to all aspects of the present invention.

[0063] In this specification, unless otherwise expressly stated, the term "about" refers to plus or minus 20%, more preferably plus or minus 10%, even more preferably plus or minus 5%, and most preferably plus or minus 2%. For example, a distance of "about 50 cm" should be understood to include distances between 45 cm and 55 cm.

[0064] In the present specification, the term "substantially" refers to a deviation of plus or minus 20%, more preferably plus or minus 10%, even more preferably plus or minus 5%, and most preferably plus or minus 2%.

[0065] In the present specification, referring to "substantially" includes referring to "entirely" and / or "exactly." That is, in the case where the word "substantially" is included, it should be understood that this also includes a reference to a specific sentence not including the word "substantially".

[0066] It should be understood that various changes and modifications to the currently preferred embodiments described herein will be apparent to those skilled in the art. Such changes and modifications may be made without departing from the spirit and scope of the present invention and without weakening its incidental advantages. Therefore, it is intended that the appended claims cover these changes and modifications.

Claims

1. A pellet for an injection molding composition, wherein the pellet has a substantially elongated shape and comprises a core-shell structure, wherein: i) the core of the pellet is formed from a thermoplastic composition comprising a polyetheretherketone polymer (PEEK polymer), the core having a width dimension in the range of about 1 mm to about 4 mm, and ii) the shell of the pellet is formed from a powder coating, the powder coating comprising calcium stearate, wherein the shell has a thickness in the range of about 5 μm to about 45 μm, wherein the calcium stearate is present at about 0.03 wt% to about 0.05 wt%, and wherein the longitudinal dimension of the pellets is in the range of about 1 mm to about 6 mm.

2. The granule of claim 1 or claim 2, wherein the calcium stearate is present in an amount of about 0.04 wt%.

3. A pellet as claimed in any preceding claim, wherein the shell comprises 1 to 3 coating layers, wherein the thickness of each layer is in the range of about 5 μm to about 15 μm.

4. A pellet according to any preceding claim, wherein the shell has a thickness in the range of about 10 μm to about 30 μm, preferably in the range of about 15 μm to about 25 μm.

5. The granule according to any one of the preceding claims, wherein the calcium stearate forming the powder coating has a D50 particle size of about 8 μm to about 10 μm, and a D90 particle size of about 18 μm to about 20 μm.

6. A pellet as claimed in any preceding claim, wherein the pellet is substantially cylindrical.

7. A pellet as claimed in claim 6, wherein at least one end of the pellet is wedge-shaped.

8. The pellet of claim 6 or 7, wherein the diameter of the pellet is in the range of about 2.5 mm to about 3.5 mm, and wherein the longitudinal dimension of the pellet is in the range of about 2 mm to about 4 mm.

9. The pellet of any preceding claim, wherein the pellet has a mass in the range of about 0.02 g to about 0.05 g.

10. A pellet as claimed in any preceding claim wherein the PEEK polymer is semi-crystalline.

11. A granule as claimed in any preceding claim wherein the powder coating of calcium stearate forming the shell is a dry solid powder which is substantially continuous across the surface of the granule.

12. The pellet of claim 11, wherein the powder coating adheres to the surface of the pellet only by contact forces.

13. A pellet as described in any of the preceding claims, wherein the thermoplastic composition further comprises about 0.1 wt% to about 50 wt% of a filler, preferably about 0.1 wt% to about 30 wt% of a filler, wherein the filler is carbon black, glass fiber, a mineral filler or a combination of two or more thereof, preferably wherein the filler is carbon black.

14. A pellet as claimed in claim 13, wherein the filler is carbon black and is present in an amount ranging from about 0.5 wt% to about 5 wt%.

15. A plurality of pellets comprising the pellets of any preceding claim, wherein at least about 99% of the pellets have a length of about 2 mm to about 4 mm.